Antimicrobial activity of extracts and alkaloids from callus and shoot cultures of Ruta angustifolia (L.) Pers - Mohd Hassan, Norazian; Abdol Latif, Fatimah; Tuan Aziz, Wan Hazni; Mohd Noor, Siti Sarah; Mohd Kamal, Laina Zarisa; Darnis, Deny Susanti (2012)
Ruta angustifolia (L.) Pers., which is known as Garuda in Malaysia or Inggu in Indonesia is the only species in the genus Ruta of Rutaceae family that can be found in tropical climate. In Malaysia, it is usually grown as pot plant and use medicinally to treat skin diseases, boils and ear infection. In-vitro callus and shoot cultures have been established from its stem explants. Both tissues were multiplied, harvested and freeze dried for consecutive extraction with hexane, dichloromethane and methanol. The crude extracts from both tissues and intact plant were screened for their antimicrobial activity by disk diffusion assay against Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 11778, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 90028 and Candida parapsilosis ATCC 22019. The antimicrobial active compounds were isolated following bioassay-guided isolation approach. Agar overlay bioautography assay was performed to screen for the antimicrobial active compounds and the targeted active compounds were isolated by column chromatography. The antimicrobial activity of the isolated compound was evaluated quantitatively by using broth microdilution assay. The crude extracts of the in vitro cultures showed various degree of activity against the tested microbes and better activity as compared to that of intact plant. Three antimicrobial active alkaloids were isolated and identified as arborinine, graveoline and skimmianine. The alkaloids showed activity against all tested microbes with minimum inhibitory concentration (MIC) ranged between 62.5 µg/ml and 1000 µg/ml.